APLIKASI SISTEM PAKAR DALAM MENDIAGNOSIS PENYAKIT KULIT PADA MANUSIA BERBASIS VISUAL - Rozi Meri (JURNAL ILMIAH INFORMATIKA, 2021)
Health is a blessing that is very important for humans, most of us, many of us don't really care about skin diseases caused by fungi such as tinea versicolor, water fleas, ringworm and scabies. In general, people are quite aware of how to deal with the symptoms of skin diseases suffered. But it would be better to include medical participation in detecting a disease symptom, because many disease symptoms are considered trivial by some people but can be fatal to human skin. So it is necessary to make an application based on medical knowledge to diagnose skin diseases in humans which is used as a tool in obtaining information about skin diseases in humans and provide recommendations as the first action that must be taken to repeat skin diseases in humans. The knowledge base is structured in such a way into a database with several tables. Drawing conclusions in this expert system using the forward chaining inference method. The expert system will provide questions to the user in the form of symptoms of several diseases and the user will answer these questions. Until the user will get a solution from the results of the question earlier.